PENGARUH KOMPETENSI KARYAWAN, ETIKA BISNIS ISLAM TERHADAP KUALITAS PELAYANAN NASABAH BANK SYARIAH INDONESIA DI MUARA BULIAN KABUPATEN BATANG HARI - El Munawwarah, El Munawwarah; Sari Asmara, Wina; Hebat Kurnia , Raden (Program Studi Ekonomi Syariah, 2025)
This research is based on the quality of service provided by the Bank to customers. There are many influences that make the service of BSI Muara Bulian Branch quality, including in terms of employee competence and Islamic business ethics owned by the Bank. The purpose of this study is to determine how much influence employee competence and Islamic business ethics have on the quality of customer service at BSI Muara Bulian Branch. The research method used is a quantitative method. The population used in this study were active customers at BSI Muara Bulian Branch using the Slovin theory with a 5% error limit, a sample of 164 respondents was obtained with a trial of 30 respondents through random sampling techniques and the remaining 134 respondents were used again as a test of the research instrument. The data collection techniques used by the researcher were literature studies, observations, interviews and questionnaires. Based on the results of the study, it shows: the influence of employee competence on service quality is 34.2%, the influence of Islamic business ethics on service quality is 65.4%, and simultaneously employee competence and Islamic business ethics on service quality have an effect of 81.1%